2009
DOI: 10.1111/j.1528-1167.2009.02260.x
|View full text |Cite
|
Sign up to set email alerts
|

Spike–wave discharges are necessary for the expression of behavioral depression‐like symptoms

Abstract: SUMMARYPurpose: The WAG/Rij strain of rats, a wellestablished model for absence epilepsy, has comorbidity for depression. These rats exhibit depression-like behavioral symptoms such as increased immobility in the forced swimming test and decreased sucrose intake and preference (anhedonia). These depression-like behavioral symptoms are evident in WAG/Rij rats, both at 3-4 and 5-6 months of age, with a tendency to aggravate in parallel with an increase in seizure duration. Here we investigated whether the behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
102
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 62 publications
24
102
2
2
Order By: Relevance
“…The results of Blumenfeld et al were later confirmed by another research group using an identical protocol (Sarkisova et al, 2010); in this case, the development of absence seizures was associated with the development of behavioral depression-like comorbidity, and when rats were followed up to 47 days after ETH withdrawal, a 74% seizure reduction was still observed at that age. To be noted in the Blumenfeld et al study at 30 days, an ~85% seizure decrease (Figure 2) was observed while at 60 and 90 days after ETH suspension, about 50% and 60% reduction was seen respectively, in comparison to untreated controls as can be evidenced from their figures (Blumenfeld et al, 2008).…”
Section: Drug Efficacy Against the Development Of Spontaneous Absencesupporting
confidence: 69%
“…The results of Blumenfeld et al were later confirmed by another research group using an identical protocol (Sarkisova et al, 2010); in this case, the development of absence seizures was associated with the development of behavioral depression-like comorbidity, and when rats were followed up to 47 days after ETH withdrawal, a 74% seizure reduction was still observed at that age. To be noted in the Blumenfeld et al study at 30 days, an ~85% seizure decrease (Figure 2) was observed while at 60 and 90 days after ETH suspension, about 50% and 60% reduction was seen respectively, in comparison to untreated controls as can be evidenced from their figures (Blumenfeld et al, 2008).…”
Section: Drug Efficacy Against the Development Of Spontaneous Absencesupporting
confidence: 69%
“…An exception might be the chronic treatment with ethosuximide (ETX). It might interfere with epileptogenesis as was suggested by outcomes from several experimental studies in the genetic models (Blumenfeld et al, 2008;Sarkisova et al, 2010;Russo et al, 2010). A prospective cohort study in children with CAE showed that long lasting ETX treatment resulted in a higher rate of complete remission and in more occurrences of five and ten year remission, suggestive for an anti-epileptogenic effect (Berg et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the antiepileptogenic effects of chronic ETX was accompanied by a decrease in depressive-like behaviour in WAG/Rij rats (Sarkisova et al, 2010;van Luijtelaar et al, 2013). Considering that epileptogenesis and chronic ETX treatment inducing antiepileptogenesis might affect mood and cognitive processes such as learning and memory, these latter processes were additionally investigated in a cue discrimination learning task in an Y-maze (problem solving task) and in a sucrose motivation task during and after chronic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding WAG/Rij rats, it has also been hypothesized that some common, currently unknown, mechanisms could be responsible for the appearance of absence seizures and low-grade depression (dysthymia) in this strain, with seizure activity being required for the expression of depressive-like behavior [26,72] even though some exceptions exist [27,40,41]. Based on this background, the antidepressant effects of fingolimod observed after an ELTT in WAG/Rij rats could be linked to its temporary antiepileptogenic effects, which disappear with seizure reappearance 4 months later, rather than to a direct effect.…”
Section: Discussionmentioning
confidence: 99%